What's a coach to do? Exploring coaches' perspectives of body image in girls sport. (May 2020) - Sabiston, Catherine M.; Lucibello, Kristen M.; Kuzmochka-Wilks, David; Koulanova, Alyona; Pila, Eva; Sandmeyer-Graves, Allison; Maginn, Drew
Abstract: Adolescent athletes report body image concerns that negatively impact their sport experiences and participation. The coach's perspective may be informative to how the context of sport perpetuates, supports, or protects from negative body image. Yet few coaches are represented in this area of research. The purpose of the present study was to explore coaches' perceptions of body image in girls sport. Thirteen coaches with an average of 10 years of experience working with girls in primarily non-aesthetic team sports were interviewed. Based on inductive thematic analysis, coaches' perceptions of the athletes' body image concerns were reflected in four themes labelled (i) body image: the 'elephant' on the field (i.e., identifying the unspoken nature of body image), (ii) agents of body image in sport (i.e., parents, coaches, and media), (iii) skill over appearance (i.e., focusing on athletic skill and competence), and (vi) systemic strategies. This last theme offers several considerations for improving the sport context with a lens to improve body image. Of relevance, it was apparent that all coaches operationalized body image as predicated on appearance, body shape, and weight and this narrow simplistic perception could guide future programs and practices. Taken together, findings highlight the need to intervene with coaches to provide adequate support and education on body image in girls sport. Highlights: Coaches perceive body image concerns as prevalent in girls team sports. Coaches' operationalization of body image was narrow and simplified. Resources and support for coaches to mitigate body image concerns are needed.